Cattle husbandry in Nigeria - Lhoste, Philippe; Cloe, L.; Hoste, Christian H.; Deslandes, P. (1980)
Results of trials carried out at the C.R.Z. of Minankro (Bouake) to compare meat production performance of the main bovine populations of the country divided into Baoule, Mere, N'Dama and zebu genotypes. Data on growth, efficiency of ration, adaptability and sanitary behaviour as well as meat qualities included.